Abnormal Airway Mucus Secretion Induced by Virus Infection - Li, Yao; Tang, Xiao Xiao (Frontiers in Immunology, 2021)
The airway mucus barrier is a primary defensive layer at the airway surface. Mucins are the primary structural components of airway mucus that protects the respiratory tract. Respiratory viruses invade human airways and often induce abnormal mucin overproduction and airway mucus secretion, leading to airway obstruction and disease. The mechanism underlying the virus-induced abnormal airway mucus secretion has not been fully studied so far. Understanding the mechanisms by which viruses induce airway mucus hypersecretion may open new avenues to treatment. In this article, we elaborate the clinical and experimental evidence that respiratory viruses cause abnormal airway mucus secretion, review the underlying mechanisms, and also discuss the current research advance as well as potential strategies to treat the abnormal airway mucus secretion caused by SARS-CoV-2.